Functional ingredients from Brassicaceae species: overview and perspectives - Ramirez, Daniela Andrea (2020)
Brassicaceae vegetables are important crops consumed worldwide due to their unique flavor, and for their broadly recognized functional properties, which are directly related to their phytochemical composition. Isothiocyanates (ITC) are the most characteristic compounds, considered responsible for their pungent taste. Besides ITC, these vegetables are also rich in carotenoids, phenolics, minerals, and vitamins. Consequently, Brassica’s phytochemical profile makes them an ideal natural source for improving the nutritional quality of manufactured foods. In this sense, the inclusion of functional ingredients into food matrices are of growing interest. In the present work, Brassicaceae ingredients, functionality, and future perspectives are reviewed.